Detection of atypical porcine pestivirus in semen from commercial boar studs in the United States - Gatto, I. R.H. [UNESP]; Arruda, P. H.; Visek, C. A.; Victoria, J. G.; Patterson, A. R.; Krull, A. C.; Schwartz, K. J.; de Oliveira, L. G. [UNESP]; Arruda, B. L. (Wiley, 2018)
Atypical porcine pestivirus (APPV) has recently been identified as a cause of congenital tremor (CT) in pigs and has been detected in semen and preputial swabs from boars that were known to be clinically affected with CT. Accordingly, the objectives of this study were to 1) detect the presence of APPV in semen, preputial fluids and preputial swabs from adult boars by quantitative reverse transcription PCR (qRT-PCR) and 2) genetically characterize a subset of positive samples to better understand the ecology of APPV in commercial boar studs and the potential risk of transmission of APPV via semen. A total of 597 samples of semen, preputial fluid and preputial swabs each representing a different boar were obtained from four commercial boar studs located in three different states in the United States. Viral RNA was detected by qRT-PCR in 90 samples (15.08%; 90/597), with the greatest per cent positive from preputial swabs (23.81%; 5/21) followed by preputial fluid (22.81%; 26/114) and semen (12.91%; 59/457). The mean cycle quantification (Cq) between sample types was similar while eleven semen samples had Cq values lower than 27.0 corresponding to approximately 2 × 106 copies/ml. Based on phylogenetic analysis of the Npro gene, different viral strains can be on the same farm at the same and different times. This is the first report of detection of APPV in semen from commercial boar studs. Studies investigating the role of semen in the transmission of APPV and production of CT are needed.
Keywords: atypical porcine pestivirus; pestivirus; semen